Negative and Positive Assimilation, Skill Transferability, and Linguistic Distance - Chiswick, Barry; Miller, Paul (University of Chicago Press, 2012)
This paper synthesizes two models of immigrant assimilation: “positive assimilation” if earnings rise with duration as destination-relevant skills are acquired and “negative assimilation” if immigrants with highly transferable skills experience declining earnings as their economic rent diminishes. Hypotheses are developed and tested with earnings of adult male immigrants in the 2000 U.S. Census. “Linguistic distance” from English of an immigrant’s mother tongue is the index of skill transferability. Only immigrants from English-speaking developed countries experience negative assimilation. Immigrants from other countries experience positive assimilation, the degree of assimilation increasing with linguistic distance.